2007
DOI: 10.1017/s000192400000467x
|View full text |Cite
|
Sign up to set email alerts
|

Aircraft cost modelling using the genetic causal technique within a systems engineering approach

Abstract: the airframe sub-system. The systems costing methodology is facilitated by the genetic causal cost modeling technique as the latter is highly generic, interdisciplinary, flexible, multilevel and recursive in nature, and can be applied at the various analysis levels required of systems engineering. Therefore, the main contribution of paper is a methodology for applying systems engineering costing, supported by the genetic causal cost modeling approach, whether at a requirements, functional or physical level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…Comparing this implementation with applications without KBE support [8,9,11,68], the proposed approach accelerates the integrated design and analysis process. Practices in industry for the cost estimation of a complex component need weeks to finish, while when the KB is available, this approach is immediate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing this implementation with applications without KBE support [8,9,11,68], the proposed approach accelerates the integrated design and analysis process. Practices in industry for the cost estimation of a complex component need weeks to finish, while when the KB is available, this approach is immediate.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, design and optimization studies including cost influence can also be performed within such systems. A group of researchers, including Kundu et al [7], Price et al [8], Curran et al [9], Castagne et al [10], and Early et al [11], has developed a generic cost estimation tool by integrating cost into design, multidisciplinary optimization and system engineering. Van der Laan et al [12] have integrated friction stir welding into a multidisciplinary aerospace system called the Design and Engineering Engine (DEE), building a process based model to compare the efficiency of friction stir welding and riveting process costs.…”
Section: Introductionmentioning
confidence: 99%
“…Each value lever of the set i=1…N has an associated scaling factor α i and error ε i and is in turn defined by a subset of lower level value parameters, x ji for j=1…M and associated scaling factor ω j , that describe the causal nature of each of each driver. The establishment of the lower level value parameter functions are carried out using the Genetic-Causal Approach (GCA) presented by Curran et al [3][4][5][6] . The GCA was first developed with respect to cost modelling but is particularly well suited to the evaluation of any value driver and is based on two fundamental scientific principles: a) the Genetic Principle: categorizing drivers and parameters into sets of a similar nature; and b) the Causal Principle: formalizing relationships explicitly only where cause and effect is satisfied.…”
Section: Value Operations Methodology (Vom)mentioning
confidence: 99%
“…An inspection of the full cost model has shown that the basic semantic elements of composite manufacturing technology (a combination of material and form), manufacturing breakdown structure and manufacturing process are sufficient to describe the context of a knowledge element, under the assumption that these contextual elements are developed into more detailed hierarchies for actual use (see Section 4.3). Reassuringly, this categorisation conforms to the basic elements utilised for the Genetic Causal costing methodology advanced by Curran et al (2007a). These semantic cost model elements form the context dimensions for a top-level contextual description model that can be used to structure knowledge in the knowledge management application (see Section 4).…”
Section: Cost Model Contextmentioning
confidence: 99%